Das sombras às formas : a participação da mulher no movimento sindical dos trabalhadores e trabalhadoras rurais (MSTTR) no estado de Sergipe - Melo, Agnes Santos (2009)
The country women were always in the social movements, however they are not on the registers as personages in the happenings, but as marginal actors. In the social process, the woman was seen as a marginal actor in the history with different social roles for man and woman, where he was always over then woman. However, in 1980 with social movements started in 1970 , that image started to change in Brazil when highlight women s organizations and between that organizations for country women. It was an important point for the women take part on the social movements. It has been meaning the beginning of the female participation in a field usually represented as male. Furthermore, the relationship between labor unions and female workers were not easy. Since the beginning, labor unions were a space for men. Women always had have important presence in the country life, even not recognized, but the labor unions did not join them to the day-by-day practice or share with them the power in the workers organizations. The main objective of this study consists of analyzing the ways of the women participation in the labor union movement for female and male country workers in Sergipe (MSTTR). The study connects the women difficulties to participate in the MSTTR to the socialization process and, therefore, the formulation of different role for men and women.